An Intelligent Hierarchical Cyber-Physical System for Beach Waste Management: The BIOBLU Case Study - Giovanni Cicceri; Dario C. Guastella; Giuseppe Sutera; Francesco Cancelliere; Mario Vitti; Giovanni Randazzo; Salvatore DiStefano; Giovanni Muscato (IEEE Access, 2023)
Nestled at the confluence of nature grandeur and human civilization, beaches command an influential presence that resonates throughout the environment, society, and culture. However, climate change and pollution overhang the beach health and need to be properly dealt with. Proactive measures involve education, responsible waste management, sustainable infrastructure, and environmental regulations, while reactive ones focus on immediate response and cleanup efforts. Nevertheless, continuous monitoring and cleaning are challenging due to various factors such as beach characteristics, hidden waste, weather conditions and, consequently, high costs. To overcome such challenges, this paper proposes an autonomous system for beach cleaning adopting an Intelligent Hierarchical Cyber-Physical System (IHCPS) approach and Information and Communication Technologies. The proposed beach waste management (BeWastMan) solution integrates an Unmanned Aerial Vehicle for the beach aerial surveillance and monitoring, a ground station for data processing, and an Unmanned Ground Vehicle to collect and sort waste autonomously. The research findings contribute to the development of innovative and fully automated approaches in beach waste management, and demonstrate the feasibility and effectiveness of the BeWastMan IHCPS by a real case study, developed in the frame of the BIOBLU project.